Overcoming the Boundaries: Originality of Problems and Genre Form of the Novel by V. Woolf “Flush” - E. V. Ushakova (Научный диалог)
The article considers the story of the English writer Virginia Woolf “Flush” (1933) as a kind of modernist experimental biography in which the conventions of traditional biography are parodied. The main attention is paid to the unusual choice of the hero of the biography, the Spaniel Flush, the beloved dog of Elizabeth Barrett-Browning, who gave Woolf the opportunity to ironize over “serious” biographies. It is reported that significant events in the life of the famous English poetess are shown through the eyes of her dog, on the one hand, limited by the biological characteristics of perception, on the other hand, free in its judgments. Attention is paid not only to the creative polemic of Woolf with limitations of the biographical genre, but also to how the problems of the position of women in society, also surrounded by a number of restrictions and prohibitions, are revealed in the story. An analysis of the episodes and the role of female characters demonstrates the writer’s attitude to the issue of a woman gaining freedom in society and in her own work. Two main lines of the story, related to overcoming the boundaries of both the biography genre and the restrictions that fetter a woman writer trying to realize her creative and life potential are revealed.